Mise-En-Scene Sebagai Pendukung Unsur Dramatik Film Penyalin Cahaya - Fajri, Husnil; Fitri, Dynia; Riski, Wahyu Nova (Institut Seni Indonesia Padang Panjang, 2023)
This research aims to reveal and explore the role of mise-en-scene contained in each of the dramatic elements of the film. Supporting dramatic elements (conflict, suspense, curiosity and surprise) contained in the film, seen from the aspects of mise-en-scene, namely setting, make up & costume, lighting and staging: movement & performance.This research employs a qualitative research method with a descriptive approach. The research object chosen is the Photocopier (2021) directed by Wregas Bhanuteja. The data in this study were obtained from observations, interviews and documentation of the film. The theory used in analyzing mise-en-scene is the mise-en-scene theory by David Bordwell, Kristin Thompson & Jeff Smith based on the theory of dramatic elements by Elizabeth Lutters.The results of this study indicate that there are 25 scenes containing dramatic elements based on the level of significance of the presence of mise-en-scene in supporting dramatic elements. In this film, mise-en-scene plays a role in supporting dramatic element (conflict, suspense, curiosity, and surprise) so that the audience can feel it through settings, costumes, lighting and staging arrangements : movement & performance. While the make-up applied to the film does not have a major influence on each of the film's dramatic elements.